Ashton Hall : a novel - Belfer, Lauren (Ballantine Books, 2022)
"A frustrated academic still reeling from her husband's betrayal moves into Ashton Hall with her young son and tries to come up with answers after they discover the remains of a woman walled into a forgotten part of the manor"--